(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
In the present investigation iontophoretic permeation of risedronate sodium (RS) through optimized gel based formulation was evaluated with respect to various electrical parameters like Current density and type of current. The study also involved enhancement the iontophoretic permeation of RS in combination with electroporation and chemical penetrationÂ enhancers with its inâ€vivo Pharmacokinetic evaluation.The permeation studies were carried through the human cadaver skin by using modified Franz diffusion cell and microcontroller based devices for iontophoresis and electroporation developed inÂ the laboratory. Inâ€vivo Pharmacokinetic studies were carried out in hairless rats. One way ANOVA followed by Tukeyâ€KramerÂ test for multiple comparisons. The permeation of RS was significantly increased with iontophoresis at 0.5 mA/Cm2 currentÂ density.The iontophoretic permeation was found depend on current density and ON:OFF ratio.The pulsatile current resultedÂ in high permeation than continuous current. Maximum permeation was obtained at 0.5 mA/cm2 with 1:1 pulsed current.Â When iontophoresis was coupled with chemical penetration enhancers and electroporation for 100 ms at 220V, synergisticÂ enhancement in permeation was observed with shortened lag time and high flux. The required flux was achieved withÂ area of application 1.55 cm2. Inâ€vivo studies in hairless rats revealed high Cmax, low tmax and increased area under the curveÂ with electroporation, followed by iontophoresis indicated increased bioavailability. Relative bioâ€availability was 4.6 whenÂ calculated in comparison to passive studies. Key words: Electroporation, iontophoresis, penetration enhancers, risedronate sodium